FETAL OUTCOME IN PREGNANCIES COMPLICATED BY OBESITY - Syed, Wajeeha (Journal of Postgraduate Medical Institute, 2015)
Objective: To determine the frequency of complications related to obesity infetus born to obese mother. Methodology: This descriptive cross sectional study was conducted in department of obstetrics and gynaecology, Lady Reading Hospital, Peshawar; from April, 2010 till March 2011. Total 250 consecutive antenatal patient with BMI >25kg/m2 were included in the study that fulfilled the inclusion criteria. Fetal outcomes of still birth and macrosomia were measured. Data was analyzed by SPSS version 10. Results: Obesity in pregnancy is associated with increased fetal risk of macrosomia 22% and stillbirth 8%. Conclusion: Maternal obesity is associated with increased fetal risks and complications.